AN ERROR ANALYSIS IN CHANGING ACTIVE VOICE INTO PASSIVE VOICE OF SIMPLE PAST TENSE - Holler Sinamo (Asosiasi dosen IDEBAHASA KEPRI, 2019)
The problem of the study is 1) what are the types of errors made by the students in changing active voice into passive voice of simple past tense . 2) what are the types of errors dominantly made by the students in changing active voice into passive voice of simple past tense. 3) Why are the students make error in changing active voice into passive voice of simple past tense. The objectives of the study are to find out a: 1) To find out the types of error are made by the students in changinga active voice into passive voice of simple past tense, 2) To find out the dominantly types of errors are made by the students in changing active voice into passive voice of simple past tense, 3) To find out the reasons of errors are made by the students in changing active voice into passive voice of simlpe past. Method of the study is qualitative research. The total number of students’ error in changing active voice into passive voice of simple past tense is 349 errors. Which is devided into 43 (12,32%) errors of omission, 10 (2,86%) errors of addition, 154 (44,12%) errors of misformation, and 142 (40,68%) errors of misordering. The dominant types of error are made by the students in changing active voice into passive voice of simple past tense is misformation 154 errors (44,12%). The students do errror in changing active voice into passive voice of simple past tense because the students do not know how to change the formula from active voice into passive voice of simple past tense. The students sometimes are bored with conventional method.